2009
DOI: 10.1111/j.1468-5906.2009.01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Race, Religion, and Worship: Are Contemporary African‐American Worship Practices Distinct?

Abstract: Drawing upon the cultural repertoire and religious marketplace perspectives, this study examines the extent to which ecstatic, participatory worship practices are distinctive to African‐American congregations and explores the role that ecstatic, participatory worship plays in contemporary African‐American worship. National Congregations Study (NCS) data are used to conduct comparative analyses of African‐American and white congregations' participation in two forms of ecstatic, participatory worship: verbal aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Thus, the congregation does not merely practice ethnic reinforcement; rather, the congregation places the value of diversity at the center of the congregation in a way that recognizes the unique experience of African Americans. Recently, research has shown African‐American worship practices like spontaneous physical worship are ethnically distinct (Edwards 2009). Historically, much of the Black Church's ministry involved political mobilization and corporate empowerment since the oppression of blacks in American society is what prompted the development of the Black Church (Harris 1999; Patillo‐McCoy 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the congregation does not merely practice ethnic reinforcement; rather, the congregation places the value of diversity at the center of the congregation in a way that recognizes the unique experience of African Americans. Recently, research has shown African‐American worship practices like spontaneous physical worship are ethnically distinct (Edwards 2009). Historically, much of the Black Church's ministry involved political mobilization and corporate empowerment since the oppression of blacks in American society is what prompted the development of the Black Church (Harris 1999; Patillo‐McCoy 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Racial conflicts within religious organizations have often been framed in terms of divergent, racially-informed "cultural repertoires" or "toolkits" (e.g., Edwards 2009;Emerson and Smith 2000). These repertoires contain "symbolic vehicles" that serve to establish boundaries and personal identities for members of racial/ethnic groups.…”
Section: Habitus Conflict and Hegemony Within Interracial Religiousmentioning
confidence: 99%
“…Table I lists numerous studies of how group prayer helps individuals cope, heal, refuel, or find freedom, but there has been little or no research on whether/how group prayer helps the praying group cope with collective stresses, heal from traumatic events, refuel its shared effervescence, or discern "godly" decisions to make about its functioning or future. 43 Poloma & Green (2010), Edwards (2009:47-48), Carle (2001), Pope (1942:123-4). 44 Warner (200), Wolff (1991, Williams & Pollio (1999), Carroll (1999), Kubicki (1997:201-202), Csorda (1997, Edwards (2009:48).…”
Section: The Content Of Group Prayermentioning
confidence: 99%
“…Is it deprived and oppressed levels of society Nelson 2005;Edwards 2009) or is lack of existential security not the only reason urging people to pray )? Yet again, how does prayer influence people's lives and public presence?…”
Section: Is Prayer Not Just One Religious Practice Among Others?mentioning
confidence: 99%